BIOTEMAS nas Escolas: Um panorama das atividades desenvolvidas pelo curso de Geografia (Unimontes) no período de 2018 a 2022 - Macedo, Gabriela Amorim de; Vasconcelos, Nalanda Cecília Silva; Alves, Rahyan de Carvalho (Revista Vozes dos Vales: Publicações Acadêmicas, 2024)
The "Biotemas in Basic Education" program, developed by the Department of Internships and School Practices (DEPE) of the State University of Montes Claros (Unimontes), stands out for its educational relevance by integrating students from various areas and elementary school students in public schools, in an activity that involves teaching, research and extension. This study sought to highlight the actions of the Geography course within this program between 2018 and 2022. A quantitative and qualitative approach was used to analyze the records available in the event's online annals. The survey identified actions such as mini-courses, workshops, exhibitions and stands linked to Geography. The methodological procedures adopted included a bibliographic and documentary survey, the use of geoprocessing techniques and the use of Excel software to draw up tables. The results were presented in the form of maps, tables and analyses of the geographical sub- areas involved. The activities covered various sub-fields of Geography, with Physical Geography featuring prominently. The study reveals the Geography course's commitment to the Biotemas program, addressing various themes, but highlights the expository methodological concentration in the partner schools. It also highlights the restriction of activities in 2020 and 2021, as a result of the covid-19 pandemic.